Nationwide analysis of sex differences in waiting times for cataract surgery in Sweden between 2010 and 2022 - Philip Jute; Gustav Stålhammar (Communications Medicine)
Abstract Background Sex-based disparities in healthcare access remain a global challenge. We aimed to investigate differences in waiting times for cataract surgery between males and females in Sweden, hypothesizing that such disparities might persist even within a universal healthcare system. Methods We performed a nationwide retrospective cohort study using data from the Swedish National Cataract Register, which includes over 93% of all cataract surgeries. A total of 1,413,652 patients over 40 years of age who underwent cataract surgery between 2010 and 2022 were included. Exclusions were applied to those with waiting times exceeding 24 months and those residing outside Sweden. The primary outcome was waiting time between preoperative assessment and surgery, stratified by visual acuity, region, and demographic and clinical factors. Results Here we show a mean waiting time of 64 days (standard deviation 126) for females and 60 days (standard deviation 102) for males (P < 0.001). This difference persists across all visual acuity strata and regions. A linear mixed-effects model with region as a random intercept indicates that males have a 3.3-day shorter waiting time compared to females (P < 0.001). Multivariate hazards regression identifies female sex, older age, specific comorbidities, and region of residence as significant predictors of longer waiting times. Although overall waiting times decrease over the study period, the sex-based gap remains consistent. Conclusions We observe a persistent, albeit small, difference in waiting times favoring males. These findings highlight a systemic disparity that warrants further investigation and targeted interventions to ensure equitable access to cataract care.